If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + -3n = -48 Solving 19 + -3n = -48 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-19' to each side of the equation. 19 + -19 + -3n = -48 + -19 Combine like terms: 19 + -19 = 0 0 + -3n = -48 + -19 -3n = -48 + -19 Combine like terms: -48 + -19 = -67 -3n = -67 Divide each side by '-3'. n = 22.33333333 Simplifying n = 22.33333333
| M+39=4(-4m-3) | | 2(-4*-3-13)= | | X+93=90 | | -9(-16-f)=(1-3f) | | 4[x+4]=12 | | 3y=0-2x | | 25x^2+70x+49=18 | | -2x+41+6x+8x=-19 | | 90=1500r+2 | | (5f+8)=4 | | 2=35+b | | 3x+2y+5x+2=180 | | -7+4(2k+6)=81 | | 845=3x-400 | | 14=-2(4y+5) | | -6.7x+8-7.1y-15-9.2x= | | 5x+7x-68=51-5x | | 7x-2(x-3)=56 | | -3(a-7)=-5a+11 | | Xsquared=30 | | 3r+2=42 | | 5(-2d+2)=80 | | (4x-3)+4=7 | | x^2+4x+9=2x^2-6x+14 | | 27x+72=180 | | 2x-(-15)=45 | | -7x-3+6-2x= | | 2x+13=66+45 | | -16t^2+96t+256=0 | | -2(t-5)+5t=8t-7 | | 10(-.4+.1x)=.2x | | 20-9=x+10x |